2018
DOI: 10.1097/md.0000000000009744
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability in normal tension glaucoma

Abstract: Primary vascular dysregulation (PVD) is believed to be a main cause of local vasospasm and impaired autoregulation as a possible contributing factor in the pathogenesis of normal tension glaucoma (NTG). Subjects with PVD respond stronger to psychological stress. Autonomic dysfunction is another reason of instable ocular blood flow and may be studied by means of assessment of heart rate variability (HRV) especially during a hand-cold provocation test (CPT).To compare the shift of HRV parameters in NTG and healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…We analyzed the relationship between fALFF and RNFL, C/D ratio, MD, and PSD to investigate the value of rsfMRI-fALFF in the diagnosis of NTG. The pathological basis of NTG-induced visual function damage is mainly a RNFL defect and optic disc damage (24)(25)(26). OCT can accurately determine the RNFL thickness and optic disc parameters around the optic disc, with high resolution.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed the relationship between fALFF and RNFL, C/D ratio, MD, and PSD to investigate the value of rsfMRI-fALFF in the diagnosis of NTG. The pathological basis of NTG-induced visual function damage is mainly a RNFL defect and optic disc damage (24)(25)(26). OCT can accurately determine the RNFL thickness and optic disc parameters around the optic disc, with high resolution.…”
Section: Discussionmentioning
confidence: 99%
“…have shown that patients with normal-tension glaucoma have autonomic dysfunction, with a predominance of sympathetic activity. 30 Azam MA et al. showed that meditation improves parasympathetic function.…”
Section: Discussionmentioning
confidence: 99%
“…For assessment of HRV parameters and their subsequent generalization, including other hemodynamic parameters, the standard deviation of normal-normal intervals (SDNNs) index is the mean of all the normal rate-to-rate intervals in echocardiography recording in milliseconds of the standard deviations of all the normal rate-to-rate intervals. 33 35 …”
Section: Methodsmentioning
confidence: 99%